Diplomasi Soft Power Indonesia dalam Melanesian Spearhead Group terhadap United Liberation Movement for West Papua - Muhammad Afif Maulana Roziqi; Mohamad Rosyidin (Journal of International Relations Diponegoro, 2020)
Fiji, Papua New Guinea, Solomon Islands and Vanuatu are countries in the SouthPacific that share ethnic, racial and cultural similarities. With historical burden that had beencolonized by the western nations, they formed the MSG to take their own sovereignty. Papuawhich is part of Indonesia have Melanesian ethnicity are considered to have no sovereignty oftheir own. So ULMWP wants to get independence from Indonesia and got supported by severalMSG member countries. Therefore, Indonesia has an interest to cease ULMWP byapproaching MSG members using Soft Power. Soft Power is a way to get the desired resultsthrough cultural, domestic values and foreign policy. This research argues that Indonesia usecultural and foreign policy that have succeeded in reducingsome member of MSG support toULMWP